Mapping of residential double skin façade design - Bramasta Putra Redyantanu (ARTEKS : Jurnal Teknik Arsitektur, 2023)
This paper aims to trace and map the variety of Double Skin Façade (DSF) in residential designs in Indonesia. This response to issues regarding technology development, design strategy, and the role of DSF in buildings related to aesthetic, environmental, and materiality issues in design practice. A qualitative approach with a descriptive observation case study method was conducted on various modern residential architectural designs buildings in Indonesia to illustrate how designers positioned this double skin facade in their design. The connection between the DSF with tectonic, aesthetic, sustainability, and environmental issues is shown in this study. This paper set the study boundaries for exploring residential designs' typology because the limited scale project allowed the designer to have considerable flexibility and exploration of creativity. The residential architectural design also allows the role of the DSF to be integrated with a passive design strategy, compared to commercial or public building design. The findings suggest various strategies and design exploration mapping related to DSF design. The results show that it can form a new character for contemporary Indonesian architecture and become a catalogue of exploratory, strategic, and responsive design elements in its practices.